The Influence of Interpersonal Communication and Service Quality on Library Satisfaction at Universitas Negeri Medan - Amin, Afriadi; Batubara, Abdul Karim; Fathurrahman, Muslih; Suyono, Hanny Chairany; Adellia, Mayranda; Afriyani, Wilda (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: This research uses an effective understanding of interpersonal communication and finds out what influences library users to visit the library at Universitas Negeri Medan.Objective: The purpose of this study was to analyze the effect of interpersonal communication and service quality on library satisfaction at Universitas Negeri Medan.Methods: This data collection technique is through observation and documentation. This data analysis technique uses thematic analysis. In providing services, librarians must foster positive, transparent, and interpersonal relationships by providing services that make librarians very happy when visiting the library. Communication is one of the most important factors in working between humans and other people in the work environment, for example, between employees in the same position or employees in different positions. The purpose of this research is to obtain information or feedback and improve user-friendly services, which is a form of collaboration between users and librarians to understand the purpose and objectives.Results: The results of this study prove that the most important thing is the positive influence of positive service to visitors and the quality of service to the accuracy of consumers can be well received.Conclusion: Based on the results of the research, a desktop-based information system application can be produced that can handle library services, among others, such as membership registration services, loans, returns, storage, library catalogue services, and compensation services.